Extraction of essential oil from orange peels - Ong, Hui Fong (2012)
The microwave-assisted solvent extraction (MASE) technique is a promising technique which is highlighted by increased extraction yield, decreased time and solvent consumption; moreover the reproducibility is better. Isolation of citrus essential oils from orange peels was analyzed by gas chromatography-mass spectrometry (GC-MS). It was found that main constituents in orange oil which separated by using deionized water solvent is limonene. Further studies also revealed that yield of essential oils were mainly influenced by different extraction temperature, time and power. Limonene products are being used in a wide range of industrial, institutional, commercial, medical and residential cleaning applications. In this study, this product has been developed as a natural soap and air freshener.